Hydrogen permeation properties of Pd-coated Ni60Nb30Ta10 amorphous alloy membrane - Kim, K. B.; Kim, K. D.; Lee, D. Y.; Kim, Y. C.; Fleury, E.; Kim, D. H. (ELSEVIER SCIENCE SA, 2007)
The hydrogen permeability of a melt-spun Ni60Nb30Ta10 (numbers indicate at.%) amorphous alloy has been examined in the temperature range of 573-673 K and pressures up to 0.6 MPa. Pd60Cu40 alloy membranes were also evaluated in the same manner. The permeated hydrogen flux was increased with increasing the temperature and the difference of hydrogen pressure between the feed side and permeate side of the membrane. The maximum hydrogen permeability of the Ni60Nb30Ta10 glassy alloy was 4.13 x 10(-8) mol/m s Pa-1/2 at 673 K, which was almost twice the permeability of Pd60Cu40 alloy measured under the same conditions. These permeation characteristics imply the possibility of future practical application ofthe glassy alloys as the hydrogen separation membrane. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ABSORPTION